2020
DOI: 10.1186/s12873-020-00382-3
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and return to work in patients transported by emergency ambulance after involvement in a traffic accident

Abstract: Introduction/background Traffic accidents constitute a common reason for injury. Little is known about long-term outcomes for patients following a traffic accident. Therefore, in this present paper, we examine 1-day, 30-day and 1-year mortality, and return to work (RTW) during a 1-year period. Methods Patients (between 18 and 65 years of age) who had an ambulance dispatched to them following a traffic accident and who were employed prior to the accident were identified from the Electronic Prehospital Emergenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…This variation can be attributed to differences in study populations, variability in follow-up times, and country-specific contexts. Some extreme cases are worth noting, such as a 2020 study in Denmark, where only 7.3% of patients referred by ambulance after a road accident did not return to work [26], and a study in Norway in 2007, which reported a high proportion of 72% at 12 months for patients with severe injuries…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This variation can be attributed to differences in study populations, variability in follow-up times, and country-specific contexts. Some extreme cases are worth noting, such as a 2020 study in Denmark, where only 7.3% of patients referred by ambulance after a road accident did not return to work [26], and a study in Norway in 2007, which reported a high proportion of 72% at 12 months for patients with severe injuries…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have also observed that the length of hospital stay or time in intensive care was a significant factor associated with NRW among road accident victims [19] [24] [26] [27]. In a 2020 study in Denmark, hospitalization for more than one day was significantly associated with NRW [26].…”
Section: Y Glèlè-ahanhanzo Et Al Open Journal Of Preventive Medicinementioning
confidence: 99%